The effect of corporate brand reputation on brand attachment and brand loyalty: automobile sector - Loureiro, S. M. C.; Sarmento, E. M.; Le Bellego, G. (Cogent Business and Management, 2017)
The current study aims to analyze the effect of corporate brand reputation on brand attachment and brand loyalty considering the automotive sector and the brands Tesla, Toyota, and Volvo. A sample of 327 participants, members of car brand communities, collaborate in a survey. Overall findings reveal that the perception of corporate brand reputation is more effective on enhancing brand loyalty than brand attachment. However, the effect could depend on the car brand strategy. We may also claim that customer citizen helping others is one of the most important corporate attributes perceived by customers of the three brands. Limitations and suggestions for further research are also provided.